2020
DOI: 10.15244/pjoes/118204
|View full text |Cite
|
Sign up to set email alerts
|

How Adding Biochar Improves Loessal Soil Fertility and Sunflower Yield on Consolidation Project Land on the Chinese Loess Plateau

Abstract: Although a land consolidation project has increased arable land area in loess areas, the loessal soil has poor fertility and productivity. Soil degradation and the accompanying decline in crop yields are the main limiting factors for agricultural development on the Loess Plateau. Biochar has been used as an amendment to improve soil fertility and crop yields. A potted experiment was carried out to study the effects of biochar addition (0, 5, 15 and 25 t ha −1 ) on soil physicochemical properties as well as sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Several studies have previously reported changes (increase or decrease) in pH level resulting from the application of different biochar rates [16]. Consistent with our study, a decrease in soil pH after biochar addition was observed by Qiang et al [17]. Soil pH variation after biochar application influences the microbial activity and enzyme production in addition to carbon and nutrient availability [18].…”
Section: Soil-and Plant Growth-related Parameters Of Experimentssupporting
confidence: 91%
“…Several studies have previously reported changes (increase or decrease) in pH level resulting from the application of different biochar rates [16]. Consistent with our study, a decrease in soil pH after biochar addition was observed by Qiang et al [17]. Soil pH variation after biochar application influences the microbial activity and enzyme production in addition to carbon and nutrient availability [18].…”
Section: Soil-and Plant Growth-related Parameters Of Experimentssupporting
confidence: 91%
“…Biochar is an environmentally friendly black carbon derived from the pyrolysis of raw materials (manure, organic wastes, crop residues, and bioenergy crops) in oxygen-deficient conditions [ 28 , 29 , 30 , 31 ]. The abundant micropore structure of biochar, the aromatic structure, and the largest surface area adjust the soil physical aspects [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%